Perlindungan Hukum Terhadap Konsumen dalam Pengiriman Hewan Peliharaan Melalui Perusahaan Ekspedisi - Shinta Ayu Pratiwi, Dwi; Wahyu Muhammad, Danang (Magister Kenotariatan, Universitas Jambi, 2026)
This study examines the legal responsibility of expedition companies for the safety of pets during delivery using the services of PT Kereta Api Logistik (KALOG). The research discusses the compliance of KALOG’s transport procedures with existing regulations and the company’s liability for pet deaths during shipment. The study employs a normative and empirical legal method with a descriptive qualitative analysis. The findings show that although KALOG’s procedures follow legal provisions, negligence still occurs, causing consumer losses, as in the case of three Saint Bernard dogs’ deaths due to improper packaging. Based on Law No. 23 of 2007 and Article 1365 of the Civil Code, the expedition company is obliged to provide compensation for damage or animal death as part of its absolute liability in transportation.